2007
DOI: 10.1089/aid.2006.0283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV Type 1 Infection on Hematopoiesis in Botswana

Abstract: Clinical observations suggest that HIV-1 infection causes higher anemia rates in patients in southern Africa than in those in the United States. To explore this difference we performed a cross-sectional exploratory study on the effect of HIV-1 infection on hematopoiesis in Botswana by examining hematological presentation, HIV disease state, hematopoietic progenitor cell number, and circulating viral levels in HIV-infected patients and HIV-uninfected controls. We found significant associations between CD34(+) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…[2][3][4] Recent findings by our group demonstrated that HIV-1 infection was directly associated with hematopoiesis in HIV-infected patients in Botswana, a country in southern Africa. 5 The study found direct positive associations between CD4 ϩ and CD34 ϩ cell levels, and between CD34 ϩ /CD4 ϩ dual-positive cell levels and both hemoglobin counts and colony-forming ability, as well as negative correlations between circulating viral levels and all indicators of HIV infection and hematopoietic health tested. 5 These results suggested a direct role for HIV-1C in the hematopoietic process that was not due to host population differences.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…[2][3][4] Recent findings by our group demonstrated that HIV-1 infection was directly associated with hematopoiesis in HIV-infected patients in Botswana, a country in southern Africa. 5 The study found direct positive associations between CD4 ϩ and CD34 ϩ cell levels, and between CD34 ϩ /CD4 ϩ dual-positive cell levels and both hemoglobin counts and colony-forming ability, as well as negative correlations between circulating viral levels and all indicators of HIV infection and hematopoietic health tested. 5 These results suggested a direct role for HIV-1C in the hematopoietic process that was not due to host population differences.…”
Section: Introductionmentioning
confidence: 77%
“…5 The study found direct positive associations between CD4 ϩ and CD34 ϩ cell levels, and between CD34 ϩ /CD4 ϩ dual-positive cell levels and both hemoglobin counts and colony-forming ability, as well as negative correlations between circulating viral levels and all indicators of HIV infection and hematopoietic health tested. 5 These results suggested a direct role for HIV-1C in the hematopoietic process that was not due to host population differences. We theorized that these associations, as well as the increased anemia rates seen in southern Africa, were related to an expansion of the cell tropism of HIV-1C to infect hematopoietic progenitor cells (HPCs).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…A negative correlation between circulating viral levels and density of colony forming ability, as well as an association between HPC infection and anemia, has been shown in HIV-1C-infected subjects. 2 This suggests that HIV-1 infection of HPCs can affect hematopoiesis and colonyforming ability. The observance of no correlation between circulating viral level and density of colony formation in our population further supports our conclusion that HIV-1A and HIV-1D do not preferentially infect HPCs over mature HIV target cells in vivo.…”
Section: Mullis Et Almentioning
confidence: 99%
“…1 The ability of HIV-1 to infect these hematopoietic progenitor cells (HPCs) has been investigated as a potential cause of the many hematopoietic abnormalities observed in infected individuals. [2][3][4][5] HIV-1 has been detected in a variety of hematopoietic progenitor cell types suggesting that HIV-1 is capable of infecting HPCs. 3,4,6,7 However, other studies have not detected HIV-1 infection in HPCs leading to questions about the relevance and extent of HPC infection in vivo.…”
mentioning
confidence: 99%